Design and implementation of a project management training program to develop workforce ready skills and career readiness in STEM PhD students and postdoctoral trainees - Salm, Elizabeth J.; McKinney, Caleb C. (Frontiers in Education, 2024)
A growing number of STEM doctorates pursue careers across the broader biomedical workforce, including industry, policy, and healthcare. Graduate and postdoctoral trainees need training to develop professional skills that prepare them for diverse workforce options. Through engagement with faculty and trainees, we determined that formal management skills are underdeveloped in trainees, particularly around managing projects in a way that is translatable to broader industries. At Georgetown University Medical Center, we adapted Kern's six-steps of curriculum design to develop the Academy for Transferable Management Skills (ATMS) program to help graduate and postdoctoral trainees develop linear experience in utilizing project management tools in their academic research contexts. ATMS includes a self-paced online CANVAS course with learning objectives and content modules that map to the project management cycle from initiation to closure, developed in consultation with PhD-level industry experts. From 2021-2024, 25 trainees have completed the ATMS program, including the capstone project and posttest evaluation. Trainees also complete brief quizzes after each module as a formative assessment of learning. The pre-test evaluation (n = 92) revealed a baseline of project management "pain points'' regularly encountered by trainees (risk management, project charters, work breakdown structures, identifying and managing project scope). Posttest data (n = 25) reveal a significant increase (p<0.0001) in project management self-efficacy measures across the aforementioned pain point scales. Notably, 100% of trainees indicated that they may/would refer the program to colleagues. ATMS offers trainees the flexibility to pick frameworks that apply to their projects with trainees planning to use project schedules (84%), Work Break Down Structures (80%), lessons learned reports (68%), and communication plans (68%) in their work. This integrated experiential learning approach equips trainees to develop and execute their projects according to industry-informed project management principles, which allows them to perform their current research more efficiently and to utilize project management frameworks in a way that is directly transferable to broad careers.Author ContributionsWe would like to thank the Burroughs Wellcome Fund (Grant #1020101) for funding the initial design of the Academy for Transferable Management Skills training program.